Study and Evaluation Energy Supply of PLTS and PLTB at Electrical Engineering Udayana University Bukit Jimbaran Bali - Medina, Intan Aprilia; Giriantari, I.A.D; Sukerayasa, I.W (Majalah Ilmiah Teknologi Elektro; Vol 17 No 3 (2018): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2018)
Hybrid PLTS and PLTB can overcome the demand for electrical energy, so it need a hybrid power plant (PLTH). One application of the concept of hybrid power generation with microgrid system is located at Electrical Engineering Program Faculty of Engineering Udayana University Bukit Jimbaran, Bali. This PLTH is a collaborative project between Udayana University and ESDM Ministry. PLTH in Electrical Engineering Udayana requires the study and evaluate the energy supply system from the power generation to know the performance of PLTS and PLTB. This study uses software HOMER (Hybrid Optimization Model For Electric Renewable) free trial version. A performance analysis show that PLTS and PLTB  cannot full covering the electricity load in September, October and November 2017. The real condition of electricity production from PLTS reaches 26,750.83 kWh per year, while the HOMER simulation is 35,956 kWh per year. Real condition of electric energy production from PLTB reach 4555,78 kWh per year, while HOMER simulation is bigger equal to 33521 kWh per year. The whole production of HOMER simulated electrical energy is bigger than real condition. The reduction of energy reaches 31306.62 kWh per year or 64% of the total electric loads.